2018
DOI: 10.19044/esj.2018.v14n30p338
|View full text |Cite
|
Sign up to set email alerts
|

Activité antioxydante de quelques plantes utilisées dans la région de Tiassalé (Côte d’Ivoire) dans le maintien de la santé de la peau

Abstract: Skin health is a concern for many people. This aim of this study is to evaluate in vitro the antioxidant activity of 10 plants used in cosmetopoeia for the maintenance of skin health. To achieve this objective, 30 extracts were tested using 2,2'-diphenyl-1-picrylhydrazyl radical (DPPH) and 2,2'-azino-bis (3-ethylbenzothiazoline-6) acid. -sulfonic) (ABTS + •) assays. The extracts studied were rich in total polyphenols, flavonoids, gallic tannins and alkaloids. For the DPPH reduction, 7 extracts including 5 meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…This difference in results may be due to the part of the plant used. The results obtained in this study suggested that the aqueous extract concentrates the most chemical constituent and has the ability to donate hydrogen to a free radical 17 . The presence of phtytocompounds, in this case, the flavonoids observed in this work, would justify the antioxidant activity of the aqueous extract which would be due to its richness in phenolic compounds.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This difference in results may be due to the part of the plant used. The results obtained in this study suggested that the aqueous extract concentrates the most chemical constituent and has the ability to donate hydrogen to a free radical 17 . The presence of phtytocompounds, in this case, the flavonoids observed in this work, would justify the antioxidant activity of the aqueous extract which would be due to its richness in phenolic compounds.…”
Section: Discussionmentioning
confidence: 65%
“…The presence of phtytocompounds, in this case, the flavonoids observed in this work, would justify the antioxidant activity of the aqueous extract which would be due to its richness in phenolic compounds. Several studies have demonstrated the antioxidant power of phenolic compounds and particularly flavonoids 17 .…”
Section: Discussionmentioning
confidence: 99%